Laws of Plastic Deformation Localization of Aluminum Monocrystals at Different Scale Structural Levels; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Bespalova I. Irina; Teplyakova L. Ludmila; Kunitsyna T. S. Tatjyana Semenovna; Zboykova N. Nadezhda (2016, 2016)
Title screen